DIRECTED READING THINKING ACTIVITY (DR-TA) STRATEGY TO TEACH READING - Seftika Seftika (Jurnal Smart, 2016)
This study aims to investigate the implemetation of Directed Reading Thinking Activity( DR-TA) in enhancing students’ reading comprehension. The process of DR-TA includes predicting, reading, and proving. This study employed quasi experimetal design. As the lecturer guides the process, the DRTA teaches students to determine the purpose for reading and make adjustments to what they think will come next based on the text. The finding shows that students’ reading comprehension increased after applying Directed Reading Thinking Activity( DR-TA). By using this strategy students can activate their prior knowledge of a topic/content of the text to be read, hypothesize about what might be addressed in the text, and establish meaningful purposes for reading the text. Keywords: Directed Reading Thinking Activity strategy, reading, comprehension.